2021
DOI: 10.1016/j.jmbbm.2021.104388
|View full text |Cite
|
Sign up to set email alerts
|

Cortical bone viscoelastic damping assessed with resonant ultrasound spectroscopy reflects porosity and mineral content

Abstract: Viscoelasticity is an essential property of bone related to fragility, which is altered in aging and bone disease.Bone viscoelastic behavior is attributed to several mechanisms involving collagen and mineral properties, porosities, and bone hierarchical tissue organization. We aimed to assess the relationships between cortical bone viscoelastic damping measured with Resonant Ultrasound Spectroscopy (RUS), microstructural and compositional characteristics. We measured 52 bone specimens from the femur of 26 elde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Our results suggest that Q 11 1 could be of clinical interest as it is correlated with Ct.vBMD (R 0.92 2 = , figure 4). Furthermore, Fan et al (2021) have shown that the shear wave quality factor is correlated to porosity (R 2 =0.53), and it is reasonable to infer that Q 11 1 measured in this study is also related to porosity.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Our results suggest that Q 11 1 could be of clinical interest as it is correlated with Ct.vBMD (R 0.92 2 = , figure 4). Furthermore, Fan et al (2021) have shown that the shear wave quality factor is correlated to porosity (R 2 =0.53), and it is reasonable to infer that Q 11 1 measured in this study is also related to porosity.…”
Section: Discussionsupporting
confidence: 57%
“…4). Furthermore, Fan et al (2021) have shown that the shear wave quality factor is correlated to porosity (R 2 =0.53), and it is reasonable to infer that…”
Section: Discussionmentioning
confidence: 98%
“…Another limitation of this work was the lack of validation of the shape-optimized stems obtained by the finite element simulations with other experimental or clinical assessments. Furthermore, the mechanical properties of femur bone was considered to be linearly elastic in this study, while the femur bone tissue exhibits minor viscoelastic behavior (Fan et al 2021). The viscoelastic properties of the femur bone may affect the amount of all three failure mechanisms of hip implants used as the objective functions including the stress shielding, initial relative micro-motion, and bone-implant interface stress.…”
Section: Discussionmentioning
confidence: 99%
“…Other metrics beyond HU that directly impact ultrasound propagation through the skull, such as bone porosity and mineral content 36 may allow for improved characterization of cortical and diploë bone properties. One recent study found a difference in ultrasonic imaging contrast for bones with equal porosity but varying pore size, 37 indicating that pore size variations affect the beam transmission.…”
Section: Discussionmentioning
confidence: 99%